2021
DOI: 10.1007/s10522-020-09909-4
|View full text |Cite
|
Sign up to set email alerts
|

Background radiation impacts human longevity and cancer mortality: reconsidering the linear no-threshold paradigm

Abstract: BACKGROUNDThe current linear-no-threshold paradigm assumes that any exposure to ionizing radiation carries some risk, thus every effort should be made to maintain the exposures as low as possible. Here, we examined whether background radiation impacts human longevity and cancer mortality. METHODSOur data covered the entire US population of the 3139 US counties, encompassing over 320 million people. The data on background radiation levels, the average of 5-year age-adjusted cancer mortality rates, and life expe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
1
6
0
2
Order By: Relevance
“…As indicated by the authors, such lifespan extension, established with high statistical significance (p > .005), could be associated with a decrease in cancer mortality from common malignancies, such as lung, pancreas and colon cancers for either sex, and brain and bladder cancers, for males only. 44 While the findings of this study could be influenced by the inherent assumptions in the EPA model applied in the calculation of background radiation doses, such results are in accord with and complement earlier observations from some of the world’s high background natural radiation areas in India, Brazil, China, and Iran where no, or a reverse, relationship was observed between exposure to elevated (up to 50 mSv/y.) natural background radiation and the rate of cancer mortality (reviewed by Ref.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…As indicated by the authors, such lifespan extension, established with high statistical significance (p > .005), could be associated with a decrease in cancer mortality from common malignancies, such as lung, pancreas and colon cancers for either sex, and brain and bladder cancers, for males only. 44 While the findings of this study could be influenced by the inherent assumptions in the EPA model applied in the calculation of background radiation doses, such results are in accord with and complement earlier observations from some of the world’s high background natural radiation areas in India, Brazil, China, and Iran where no, or a reverse, relationship was observed between exposure to elevated (up to 50 mSv/y.) natural background radiation and the rate of cancer mortality (reviewed by Ref.…”
Section: Introductionsupporting
confidence: 89%
“…36 Recently, a large-scale statistical study to evaluate the impact of natural background radiation on human longevity and cancer mortality has been published. 44 Individual values of dose equivalents (in mrems or mSv) from terrestrial and cosmic sources (including radon), averaged over a 5-year period (2011-2015) were evaluated for the entire population of all 3139 USA counties (involving over 320 million inhabitants) using the 'radiation dose calculator' 4 of the U.S. Environmental Protection Agency's (EPA). Data on cancer statistics over the same period were collected from the U.S. Cancer Statistics (USCS), the official federal statistics on cancer incidence and deaths, produced by the Centers for Disease Control and Prevention (CDC) and the National Cancer Institute (NCI).…”
Section: Research and Data Invalidating The Lnt Paradigmmentioning
confidence: 99%
“…In fact, exposure to low radiation doses may induce trivial stress factors to enhance protective antioxidant pathways that may contribute to longevity [ 5 , 18 ]. It has recently been determined that background radiation within the natural range of low-dose radiation increases the life expectancy by approximately 2.5 years [ 92 ]. In support of this, others have shown that LDR is involved in DNA double-stranded-break repair mechanisms [ 33 , 93 ], which can ultimately delay cell death mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Although for practical purposes this might be irrelevant, the domain of such effect is at the normal radiation background, i.e., <5 mSv y −1 (the world average human exposure is 2.4 mSv y −1 ) [ 6 ]. At this dose rate level, it was claimed that exposure might be beneficial trough adaptive response and translated in a smaller morbidity of cancer and a longer lifetime [ 29 ]. However, in the HBRAs, the effective dose rates are in the range of 5–203 mSv y −1 , or 0.01–0.55 mSv d −1 [ 4 , 30 ].…”
Section: Introductionmentioning
confidence: 99%